EVALUACIJA FAKTORA RIZIKA I PROCENA KVALITETA ŽIVOTA KOD PACIJENATA SA BAZOCELULARNIM KARCINOMOM - Loncar, Stefan D; Loncar, Dragan S (Medicinski časopis, 2015)
Introduction: Basal cell skin cancer is a malignant tumor originating from the epithelium, which is in about 80% of cases develop in the head and neck. Objective: To estimate the risk factors and quality of life in patients with cutaneous basal cell carcinoma of the head and neck. Materials and Methods: The study was conducted in a prospective study. The study included 60 patients aged 40 to 87 years, who were diagnosed with basal cell skin cancers. In all patients who were included in this study was previously conducted surgical therapy. Assessment of risk factors was analyzed from bad habits and socio-economic status. The quality of life was used Skin Cancer Index (SCI). Values ​​SCI is numerically quantified on a scale from 0 to 100. For statistical analysis of data, the T-test, and χ2 test, p <0.05 (SPSS program). Results: The consumption of alcohol was present in 45% of patients, while 32% of respondents said they consumed tobacco. Exposure to UV radiation was observed in 30% of patients. Evaluation SCI noted a decline in the quality of life in 90% of patients. In patients with the affected functional structures of the orofacial region total value of SCI was significantly lower than in those where they were not affected (p = 0.031). The prevalence of bad habits and exposure to UV radiation in this study is in accordance with contemporary literature data. In patients with cutaneous basal cell carcinoma of the head and neck there is a decreased quality of life. Keywords: Basal cell carcinoma, risk factors, quality of life